1991
DOI: 10.1121/1.401662
|View full text |Cite
|
Sign up to set email alerts
|

Tempo, stress, and vowel reduction in American English

Abstract: Two processes that affect the acoustic characteristics of vowels, namely, phonological and phonetic vowel reduction are discussed. Phonological vowel reduction applies to unstressed vowels. Phonetic vowel reduction is supposed to apply to all vowels and be caused by fast speech rates, context, as well as lack of stress. In this experiment, the effects of changes in stress and in rate of speech (tempo) on the acoustic characteristics of American English monophthongal, nonretroflex vowels were examined. Four mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 18 publications
13
99
0
1
Order By: Relevance
“…The values obtained for the stressed and reduced vowels were in agreement with those reported elsewhere for such tokens, in British English (Howell and W'tlliams, 1992), American English (Fourakis, 1991), and Dutch (van Son and Pols, 1990).…”
Section: Spectral Characteristicssupporting
confidence: 80%
“…The values obtained for the stressed and reduced vowels were in agreement with those reported elsewhere for such tokens, in British English (Howell and W'tlliams, 1992), American English (Fourakis, 1991), and Dutch (van Son and Pols, 1990).…”
Section: Spectral Characteristicssupporting
confidence: 80%
“…A substantial body of research has shown that segments produced at faster rates and unstressed syllables are more sensitive to coarticulatory effects than segments spoken at slow speech rates and in stressed syllables (Lindblom 1963, Gay 1981, Browman & Goldstein 1990, Fourakis 1991, Moon & Lindblom 1994, Byrd & Tan 1996, Davidson 2006, among many others). If postaspiration in Andalusian [h + voiceless stop] clusters is caused by changes in intergestural timing, its duration can be expected to be longer at faster speech rates and in unstressed stop consonants.…”
Section: Manipulating Speech Rate and Stress Placementmentioning
confidence: 99%
“…Quite a large body of research has shown that syllable stress and pitch accent strongly affect vowel duration and the level of vowel reduction (eg., Fourakis, 1991;Koopmans-Van Beinum, 1980;Lindblom, 1990;Van Bergem, 1995;Pols, 1990, 1992;Wang, 1997) and consonant reduction (de Jong et al, 1993;de Jong, 1995;Farnetani, 1995;Pols, 1996, 1999a). An archetypal example of reduction is that of vowel realizations becoming more like a schwa in unstressed syllables (eg., Koopmans-Van Beinum, 1980;Lindblom, 1990;Van Bergem, 1995).…”
Section: Introductionmentioning
confidence: 99%